Efforts to Increase Motivation to Learn Fiqh through the Index Card Match Learning Model at MI Raudhatul Mukminin - Mukhsin (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to investigate the effectiveness of the Index Card Match learning model in enhancing student motivation to learn Fiqh at MI Raudhatul Mukminin. Using a Classroom Action Research (CAR) approach, the study was conducted over two cycles with 25 students aged 11 to 12 years. The intervention involved using index cards with questions and answers related to Fiqh topics, which students were required to match through collaboration and discussion in small groups. Data were collected through classroom observations, pre- and post-intervention questionnaires, and informal interviews with students and the teacher. The findings revealed that the Index Card Match model significantly improved student motivation, engagement, and participation in Fiqh lessons. Students demonstrated increased enthusiasm and confidence, and the collaborative nature of the activity fostered better understanding and retention of the material. Adjustments made during the second cycle, such as simplifying questions and adding visual aids, further enhanced the effectiveness of the model. This research highlights the positive impact of interactive and cooperative learning methods on student motivation, particularly in religious education settings.